Application of Network Analysis to Evaluate the Effective Resource Management: Improving productivity and reducing costs in construction projects through network analysis (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Now a day‘s mass housing construction projects are common in India. There are so many approaches have been used for repetitive construction projects towards optimizing time and cost. In this project we have implemented a proposed theoretical model for effective utilization of labour to get optimum duration and cost. Generally critical path method is used for repetitive type of construction but in this project, we use programme evaluation review technique to find the duration of project. There are many resources which affect the project time and cost like material, money, machinery, space etc. But from the literature survey it is observed that now a day‘s the labour is major resource which affects the productivity of project. Labour absenteeism rate is about 5 to 25 in construction projects, which is vary according to the size of projects. There are so many factors affecting the labour absenteeism. The study of these factors is necessary because by studying these factors we get an idea about the labours problems. Once we know about the labour problems we can solve their problems, we can provide a various facility by which labours get satisfied. So, in this way we can reduce the absenteeism rate of labours by solving their problems and by providing good facilities to them. The goal of any construction project is to complete the project within the estimated time and with minimum cost. The delay in a construction projects affects both owner and contractor. The main goal of this study is to find out the optimum duration for the completion of project. Because we know that if the project duration is minimum then project cost is automatically reduces. In this project the data is collected from the mass housing construction project. The expected time for the completion of project is finding out by using the programme evaluation review technique. Now the collected data is analyzed and find out the optimum duration and cost. We know that the construction industry is a second largest industry in a world. The development of such industry plays an important role in a developing country like India. So, for that it is necessary to improve the productivity of construction industry.